The eurofi t sit and reach suppleness test competence of ballet school students - Szulc, Paweł; Bartkowiak, Piotr; Boch-Kmieciak, Joanna; Lewandowski, Jacek; Owczarkowska, Elżbieta (Akademia Wychowania Fizycznego w Poznaniu)
Objectives. The aim of the study is to determine the relevance of the SR test for body suppleness testing. Methods. The study sample comprised 20 female students from a ballet school and20 secondary school students who did not practice ballet, all aged 17. Their torso suppleness was tested using the SR test. The sectional mobility of the spine and hip joints was estimated with the Penny & Giles tensometric electrogoniometer. The material was analyzed statistically, and the percentage share of the respective spine and hip joint sections was determined in the performed SR test. Results. The ballet dancers were characterised by limited mobility of the cervical spine (6.5%) and the lumbar spine (49.5%) as well as an increase in the range of hip joint movement (47%) in comparison with the control group. Nevertheless, the SR test indicated greater torso suppleness in dancers (by 48%). Conclusions. In ballet dancers, unlike the controls, sit and reach test results are determined mostly by the mobility of hip joints. The disadvantage of the test is its global measurement without the percentage share of the joints. In comparison with persons without any disorders, individuals with spinal hypomobility may obtain better results owing to their hip joint hypermobility. Therefore, the abovementioned test should not be used in clinical diagnostics to assess joint mobility and muscle flexibility.
Keywords: spinal mobility; SR test; suppleness; ballet dancers; electrogoniometry